2021
DOI: 10.21511/imfi.18(1).2021.06
|View full text |Cite
|
Sign up to set email alerts
|

State debt assessment and forecasting: time series analysis

Abstract: One of the pressing problems in the modern development of the world financial system is an excessive increase in state debt, which has many negative consequences for the financial system of any country. At the same time, special attention should be paid to developing an effective state debt management system based on its forecast values. The paper is aimed at determining the level of persistence and forecasting future values of state debt in the short term using time series analysis, i.e., an ARIMA model. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…The existence of signs of chaos is noted in other processes of public finance. For example, Zhuravka et al (2021), studying the dynamics of public debt in Ukraine, confirmed a high level of fractal similarity (Hirst index is 0.74) and "long memory" of data series that was then used for further forecasting. Therefore, it makes sense to use some elements of the chaos theory in the study of dynamics of tax revenues and their forecasting.…”
Section: Literature Reviewmentioning
confidence: 91%
“…The existence of signs of chaos is noted in other processes of public finance. For example, Zhuravka et al (2021), studying the dynamics of public debt in Ukraine, confirmed a high level of fractal similarity (Hirst index is 0.74) and "long memory" of data series that was then used for further forecasting. Therefore, it makes sense to use some elements of the chaos theory in the study of dynamics of tax revenues and their forecasting.…”
Section: Literature Reviewmentioning
confidence: 91%
“…The role of public finance in ensuring the financial system's effective development and formation of stability are considered in the work of Zhuravka et al (2018). In their further study, Zhuravka et al (2021) noted that an excessive increase in public debt has negative consequences for the financial system of any country, as evidenced by the use of the ARIMA model in analyzing data on public debt in Ukraine for the period of 2004-2020. The obtained results showed an unstable debt situation, a significant increase in public debt in the last 6 years and justified the need to increase the efficiency of public debt management in the context of financial stability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…And the small weight of this indicator once again proves the need for business access to credit resources, as the interest paid by businesses to banks does not significantly affect the amount of budget revenues; 6. weighted average tariff rate on imports -despite the fact that in recent years the value of this indicator has been systematically decreasing, yet, as the results of the analysis showed, the duty rate is crucial in the formation of government revenues (Martyniuk 2011;Zhuravka, Filatova, Šuleř, and Wołowiec 2021).…”
Section: Planning and Forecasting Customs Revenues To The State Budgetmentioning
confidence: 99%